Efectos emocionales y comportamentales percibidos por padres y maestros durante y después de pandemia en estudiantes del grado 10° de la Institución Educativa Nuestra señora de Chiquinquirá. (2022)
The objective of this research work is to know the emotional and behavioral effects perceived by parents and teachers during and after the pandemic of the 10th grade students of the I.E. Nuestra Señora de Chiquinquirá. A qualitative methodology was used with a phenomenological method, in which a semi-structured interview and a questionnaire were carried out. These instruments were applied to 2 teachers and 5 parents, where we found negative emotions that were contracted from the pandemic, in addition to the mandatory preventive confinement brought consequences of anxiety, fear, anger, loss of interest in adolescents, family and school problems during these months